(untitled) (Research, Society and Development, 2021)
The form of occupation and soil management practices cause physical, chemical, and biological changes that affect the environmental and economic sustainability of the agricultural activity. Therefore, the objective was to evaluate the dynamics of leaf decomposition and microbial activity in three soil use and management systems in the Brejo, Paraíba, Brazil. The areas studied were: Agroforestry System, agricultural mandala, and native forest. The decomposition rate was determined using nylon bags containing 10 g of Gliricidia sepium leaves, which were placed on the soil surface of each area for 56 days. The leaf material was collected every seven days and taken to an oven at 65°C and weighed to evaluate the weight loss about the initial weight. The microbial activity was estimated by the quantification of carbon dioxide (CO2) released in the process of edaphic respiration, from the soil surface, and captured by the KOH solution. The Agroforestry System showed a higher decomposition speed. The system that emitted the massive amount of CO2 into the atmosphere was the mandala agricultural system. Climatic factors, such as precipitation and temperature, influence the dynamics of decomposition and the emission of CO2 released by edaphic microorganisms.